An Analysis of Deixis Found in Student English Textbook When English Rings a Bell for the Eight Grade of Junior High School - Purba, Fanny Ramayani; Sidabutar, Usman; Silitonga , Harpen (CV. Pusdikra Mitra Jaya, 2024)
The aims of this research were to determine the the type deixis and the most dominating type of deixis found in students' English Textbook For The Eight Grade of Junior High School. The design of this study is descriptive qualitative method. The source of data of this study was the conversations contained deixis found in students' English Textbook